Examination of three settlements’ marketing activities - Urbánné Treutz, Ágnes (Studia Mundi – Economica, 2016)
The theme of my analysis is three settlements situated in the Southern Great Plain Region in Csongrád County: Domaszék, Csongrád and Szeged. Based on secondary research my aim is to examine the three settlements with the help of 4Ps toolkit from the point of view of place marketing, thereby assess the marketing policies which they use. Finally I determine the target groups’ outbreak opportunities in these settlements.